Quantifying vemurafenib in dried blood spots using high-performance LC–MS/MS. (December 2014) - Nijenhuis, Cynthia M; Rosing, Hilde; Schellens, Jan HM; Beijnen, Jos H
Background: To further investigate the pharmacokinetics of vemurafenib and to support therapeutic drug monitoring an LC–MS/MS method was developed and validated for the quantification of vemurafenib in dried blood spots.Results: Vemurafenib was extracted from the dried blood spots by methanol:acetonitrile (50:50, v/v) and separated on a C18 column with gradient elution and analyzed with triple quadrupole mass spectrometry in positive ion mode. The validated calibration range is linear from 1 to 100 µg/ml. Intra- and inter-assay accuracies and precisions were within ±13.6% and ≤6.5%. The applicability of the assay was tested by analyzing dried blood spots samples of melanoma patients receiving vemurafenib.Conclusion: This assay met all predefined validation criteria and is considered suitable to quantify vemurafenib in dried blood samples.